Generation of renal tubules at the interface of an artificial interstitium - Minuth, W; Sorokin, Lydia; Schumacher, K (Cellular Physiology and Biochemistry, 2004)
During kidney development a multitude of tubular portions is formed. Little knowledge is available by which cellbiological mechanism a cluster of embryonic cells is able to generate the threedimensional structure of a tubule. However, this know-how is most important in tissue engineering approaches such as the generation of an artificial kidney module or for the therapy of renal diseases using stem cells. To obtain cellbiological insights in parenchyme development we elaborate a new technique to generate under in vitro conditions renal tubules derived from the embryonic cortex of neonatal rabbits. The aim of the experiments is to establish a specific extracellular environment allowing optimal threedimensional development of renal tubules under serum-free culture conditions. In the present paper we demonstrate features of the renal stem cell niche and show their isolation as intact microcompartiments for advanced tissue culture. Perfusion culture in containers exhibiting a big dead fluid volume results in the development of a flat collecting duct (CD) epithelium at the surface of the tissue explant. In contrast, by fine-tuning the dead fluid volume within a perfusion culture container by an artificial interstitium made of a polyester fleece shows the generation of tubules. It is an up to date unknown morphogenetic information which tells the cells to form tubular structures. Copyright (C) 2004 S. Karger AG, Basel.
The information about affiliations in this record was updated in December 2015. The record was previously connected to the following departments: Pathology, (Lund) (013030000)
Keywords: perfusion culture; polyester fleece; artificial interstitium; tubules; renal stem cells; epithelium; tissue engineering